IMF Staff papers : Volume 12 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1965)
Selections from this paper were delivered at the Annual Meeting of the American Statistical Association, Philadelphia, Pennsylvania, on September 8, 1965.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet